Peran Pengawas Sekolah dalam Pengembangan dan Evaluasi Supervisi Pengajaran untuk Peningkatan Mutu Pembelajaran - Tri Ananda Setiyani; Nur Adzkia Kamilah; Siti Raisyah; Sulistiyana Sulistiyana; Metroyadi Metroyadi (Universitas Negeri Malang, 2025)
Abstract: The role of school supervisors is a key component in ensuring educational quality through the implementation of effective instructional supervision. This article aims to describe, both theoretically and empirically, the role of school supervisors in the development and evaluation of instructional supervision, including the supporting and inhibiting factors they encounter. This study employs a descriptive qualitative approach, with the primary informant being a school supervisor at the elementary level overseeing approximately 20 schools. Data were collected through in-depth interviews, observations, and document analysis. The findings indicate that school supervisors act as mentors, motivators, and evaluators who drive supervision programs based on the needs of teachers and the schools under their guidance. The supervision program is developed through needs analysis, planning, implementation, evaluation, and follow-up, applying collaborative and reflective principles. Supervision evaluation is carried out continuously to assess the effectiveness of teacher coaching and its impact on the quality of learning. Key supporting factors include policy support and collaboration with school principals, while the main obstacles involve limited time and the large number of supervised schools. This article highlights that school supervisors play a strategic role as change agents in enhancing teacher professionalism in the era of the Merdeka Curriculum. Keywords: school supervisor; instructional supervision; supervision evaluation; learning quality Abstrak: Peran pengawas sekolah menjadi komponen kunci dalam menjamin mutu pendidikan melalui pelaksanaan supervisi pengajaran yang efektif. Artikel ini bertujuan mendeskripsikan secara teoritis dan empiris peran pengawas sekolah dalam pengembangan serta evaluasi supervisi pengajaran, termasuk faktor pendukung dan penghambat yang dihadapi. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan narasumber utama seorang pengawas sekolah di tingkat sekolah dasar dengan total kurang lebih 20 sekolah binaan. Data dikumpulkan melalui wawancara mendalam, observasi, dan telaah dokumen. Hasil penelitian menunjukkan bahwa pengawas sekolah berperan sebagai pembimbing, motivator, dan evaluator yang menggerakkan program supervisi berbasis kebutuhan guru dan sekolah binaan. Program supervisi dikembangkan melalui analisis kebutuhan, perencanaan, pelaksanaan, evaluasi, dan tindak lanjut dengan prinsip kolaboratif dan reflektif. Evaluasi supervisi dilakukan secara berkelanjutan untuk menilai efektivitas pembinaan guru dan dampaknya terhadap mutu pembelajaran. Faktor pendukung utama berasal dari dukungan kebijakan dan kolaborasi dengan kepala sekolah, sementara hambatan utama adalah keterbatasan waktu dan banyaknya sekolah binaan. Artikel ini menegaskan bahwa pengawas sekolah memiliki peran strategis sebagai agen perubahan (change agent) dalam meningkatkan profesionalisme guru di era Kurikulum Merdeka. Kata kunci: pengawas sekolah; supervisi pengajaran; evaluasi supervisi; mutu pembelajaran